Consumer Protection Against Flight Delays Resulting from Airline Operational Failures to Provide Information Services as Part of Human Rights - Arliman S, Laurensius; Ratnawati, Elfrida; Sihombing, Januardo Sulung Partogi; Multiwijaya, Vience Ratna; Razak, Aida Abdul (Arena Hukum, 2026)
Flight delays, cancellations, and unilateral flight rescheduling are persistent issues, obstructing the protection of consumer rights in Indonesia’s aviation services sector. The legal issues examined in this study are: (1) the form of legal protection for passengers affected by flight delays from a human rights perspective, and (2) the responsibility of the state and airlines in ensuring the fulfilment of passengers’ rights. Previous studies by Fahrizal et al. (2022) examined business actors’ liability for flight delays, Thoriq & Ilham (2023) focused on unilateral flight cancellations, and Budi & Siddiq (2025) analysed unilateral flight rescheduling. Although these studies share a common focus on consumer protection, they have not comprehensively integrated a human rights perspective. This study aims to analyse legal protection for airline passengers from a human rights perspective and to examine the responsibilities of airlines and the state. The research employs a normative legal research method using statutory and comparative approaches. The analytical framework is based on human rights theory, legal liability theory, and legal protection theory. The findings indicate that flight delays without fair and transparent handling constitute violations of human rights and the right to information as guaranteed by the International Covenant on Civil and Political Rights, Law No. 39 of 1999 on Human Rights, Law No. 8 of 1999 on Consumer Protection, and Law No. 1 of 2009 on Aviation, as partially amended by Law No. 6 of 2023. Airlines must be held liable in providing compensation, accommodation, or alternative flights, while the government, through the Ministry of Transportation, is authorised to impose sanctions on negligent airlines. It is recommended that the government strengthen effective complaint mechanisms to ensure the protection of passengers’ rights.